Pengaruh Dimensi dan Pre-kompresi Kayu terhadap Sifat Penyerapan Air Dimensions and Pre-Compression Wood Influences on Water Absorption - Lisman Suryanegara; Wahyu Dwianto (Masyarakat Peneliti Kayu Indonesia, 2004)
This research attempted to understand the effect of dimension and pre-compression on water absorption behavior of wood. Wood samples were water immersed at room temperature and 60°C for 48 hours in certain periods. Retention, weight gain and recovery level were observed.The results showed that water absorption mostly depended on radial and tangential area for un-compressed wood. For pre-compressed wood, the different of water immersion temperature caused recovery level differences. The retention of pre-compressed wood samples which 60°C water immersion for 48 hours were higher than that of un-compressed wood samples